Professional Development and Digital Literacy of Teachers in the Context of Digital Transformation of Education (Journal of Educational Sciences, 2025)
Digital literacy plays a crucial role in the professional development of teachers in the modern educational environment. This article analyzes the digital transformation of education within the pedagogical process and the innovative opportunities for teachers’ professional growth. Special attention is given to issues of teachers’ professional self-development and the development of information-professional skills, including the ability to manage learning based on pedagogical management, skills in creating interactive educational resources, and the development of open and mobile forms of multimedia content. The article also addresses issues related to the effective use of digital technologies, new pedagogical approaches to assessing learning outcomes, organizing online classes, implementing synchronous and asynchronous interaction in the educational process, and establishing effective feedback with learners.The research methods include literature analysis, surveys, the test “Diagnostics of the Level of Professional Orientation of Students” by T. D. Dubovitskaya, and other methods. In the empirical part of the study, a survey was conducted among 90 school teachers and students of pedagogical specializations. As a result of the experimental research, key areas of activity were identified for testing and implementing innovative opportunities for the professional development of teachers in the context of digital transformation.Keywords: education and training, digital transformation, digital literacy, educators (or teachers), digital educational resources, professional development, interactive learning resources.